"New-type" Theses in Education: Autobiographical Activations, Relationalities, and Arts as Gestures of Archiving, Performativity, and Immersion (Praxis Educativa, 2026)
The objective of this paper is to present, from an autobiographical perspective, what I call a 'new type' of thesis within the field of Education. I propose this operation through five activations that reflect immersion processes, examining what they activate and awaken within me today as a meta-analytical exercise, as well as what they synergize in readers in projective, future-oriented terms. Each activation is a thesis that uses the Arts and the de-re-co-construction of archives as a performative key to generate multiple activations—travel, cinema, music, artifacts, objects, and plants—as a means to synergize multiple assemblages and relationalities. Thus, the autobiographical condition and the restitution of meaning to a life are brought into play in the first activation; memory and fiction, concentrating the boundaries of life, define the second; the third plays with co-existentiality and life in gardened environments that represent small yet grand paradises; the fourth activation reflects the possibilities of mysticism, introspection, and imagination to mediate the position of subjects, strengthening creative processes; and finally, materialities and agential entanglements define the fifth activation, centered on the relationships we establish between things, and between ourselves and things, as a way of being, feeling, and existing in the world
Keywords: new-type thesis; education; autobiography; biographical-narrative research; relationalities